2011
DOI: 10.1002/ajpa.21508
|View full text |Cite
|
Sign up to set email alerts
|

Using the life history model to set the stage(s) of growth and senescence in bioarchaeology and paleodemography

Abstract: Paleodemography, the study of demographic parameters of past human populations, relies on assumptions including biological uniformitarianism, stationary populations, and the ability to determine point age estimates from skeletal material. These assumptions have been widely criticized in the literature and various solutions have been proposed. The majority of these solutions rely on statistical modeling, and have not seen widespread application. Most bioarchaeologists recognize that our ability to assess chrono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 82 publications
(126 reference statements)
1
31
0
1
Order By: Relevance
“…However, the methods for ageing skeletons are not good at identifying older individuals. Further analysis on identified skeletal collections is needed to determine whether using a cut-off at young adult (defined as per Roksandic and Armstrong, 2011) reduces the impact of degenerative processes, thus allowing activity-patterns to be analysed. Another method to reduce the effect of age is to study bilateral asymmetry within individuals (Villotte pers.…”
Section: Discussionmentioning
confidence: 99%
“…However, the methods for ageing skeletons are not good at identifying older individuals. Further analysis on identified skeletal collections is needed to determine whether using a cut-off at young adult (defined as per Roksandic and Armstrong, 2011) reduces the impact of degenerative processes, thus allowing activity-patterns to be analysed. Another method to reduce the effect of age is to study bilateral asymmetry within individuals (Villotte pers.…”
Section: Discussionmentioning
confidence: 99%
“…Both the Suchey-Brooks and _ Is ßcan et al methods are based on phase systems with descriptions of the degenerative changes occurring at each phase, and both have comparative casts available for purchase. Overall, researchers tend to agree that these methods are sufficiently accurate; however, many studies have found sampling issues, discrepancies in the statistical models used to create the methods, and high rates of inter-and intra-observer error (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Sex was assessed using standard morphometric methods for pelvic, cranial, and postcranial remains (Bruzek, 2002;Buikstra and Ubelaker, 1994). Age was assessed as a developmental/senescence stage (Roksandic and Armstrong, 2011). Forty-five (45) of the Canímar Abajo adults (femur samples from 14 OC and 31 YC individuals) were processed for carbon and nitrogen isotope analyses (Table 1).…”
Section: Methodsmentioning
confidence: 99%